The referendum For the independence of Kurdistan from the perspective of Islamic law and international law - اىٍدرس اىٍصاغد نارزان فلٖ خي٘و نرًٗ; اىٍدرس اىدنخٔر أردوان ٌصطفٕ إشٍاغیو (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The people's referendum for independence is a legitimate and legal right. There is no doubt that the Kurdish people in the Kurdistan Region of Iraq have the same right, but it was denied. The research strives to show the concept of the referendum and the date of its emergence and to show its standards and divisions. The study then clerified the legality of the referendum on the independence of Kurdistan from the perspective of Islamic law and international law. It explained that Islam did not stand in front of the freedom of peoples. The referendum is legitimate and supported by international law. At the conclusion of the research, the main results were highlighted, and the most prominent recommendations were made.